Closing the Spiritual Circle of Life: The Unconditional Love Revolution - Kirsch, Christiane (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2020)
This article presents and combines theories and philosophies on the spiritual rebirthing and ascension process emanating from psychology, comparative mythology, and comparative religion. It addresses various states of the soul encountered on the mystical journey to Divine Union and the various ways God assists human beings in completing this process, both personally and collectively. The analysis of the soul regeneration process — the science of the saints — addresses human sanctification during earthly existence and eventually beyond if the worldly life does not suffice to complete this process. Furthermore, the role of the Divine Feminine in salvation history is highlighted as well as the importance of the alchemical communion between divine counterparts in the inauguration of the Millennium of Peace leading toward the New Jerusalem.